Kepentingan Aktor Lokal dalam Implementasi Kebijakan Peningkatan Produktivitas Pertanian: Studi Kasus di Kelurahan Rantau Indah, Kabupaten Tanjung Jabung Timur - Anjar Dwi Arvita; Nasuhaidi Nasuhaidi; Galank Pratama; Muliono Muliono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The implementation of agricultural productivity improvement policies is an important effort to increase agricultural production and improve farmers' welfare. Policy implementation is influenced not only by program design and resource availability but also by the interests of actors involved in the implementation process. This study aims to analyze actor interests in the implementation of agricultural productivity improvement policies in Rantau Indah Village, Tanjung Jabung Timur Regency. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving representatives of the Food Crops and Horticulture Office, Agricultural Extension Workers, village government officials, farmer group leaders, and community leaders. The findings indicate that each actor has different interests in policy implementation, reflecting their respective institutional roles, responsibilities, and expectations. These differences influence program planning, coordination, decision-making, and policy execution. Nevertheless, effective communication, collaboration, and coordination among stakeholders contribute positively to minimizing conflicts of interest and supporting policy implementation. The active involvement of farmer groups and agricultural extension workers also strengthens the dissemination of agricultural innovations and encourages community participation in improving productivity. The study concludes that actor interests constitute an important factor influencing the implementation of agricultural productivity improvement policies in Rantau Indah Village. Therefore, strengthening stakeholder collaboration, improving institutional coordination, and ensuring transparent communication are essential to achieving sustainable agricultural development and enhancing farmers' welfare.